Diseño e implementación de laboratorios de computación escolares mediante el uso de computadoras recicladas y software libre educativo para los alumnos del Jardín de Infantes "José Alejo Palacios" y la Escuela "Pedro Víctor Falconí" anexos a la Universidad Nacional de Loja. - Cuenca López, Diana Maribel (2012)
This thesis project aims at implementing Computer labs with free software and recycled technology education in kindergarten "Alejo José Palacios" school "Peter Victor Falconi" annexed to the National University of Loja, for which was performed because of hardware and software inventory located in each of the computer labs, it is noteworthy that the inventory was done manually, by the side of the software is able to determine what types of programs were being used by users both laboratories, so that after the implementation of the operating system can be replaced Edubuntu 10.10 or reinstated, thanks to hardware inventory it was determined that teams were able to be used as terminals for our network of LTSP thin clients, thus began with the respective recycling of computer equipment, then proceeded to develop the network design both electrical and data for each laboratory, which was key to implementing them. Later he selected two teams for the services we provide were considered suitable to accommodate the Edubuntu OS 10.10 and on which servers were configured LTSP (Linux Terminal Server Project). Then he proceeded to configure the thin client environment, using the advantages of free software. After running the LTSP terminal network proceeded to install the boot loader 1.0.0 gPXE hard drive of some of the customers did not have the option to boot from the network and it was filled some network cards that were not in perfect condition, thanks again later and was replaced by recycling some video cards that prevented the perfect image resolution on the clients. It also taught the course on "The Edubuntu OS 10.10" to those responsible for both laboratories and delivery of user manuals and administrator, to ensure training in working with these free technologies. As part of the experience gained in this project gave a lecture in the "Second National Meeting and I Binational Ecuador-Peru Free Software" held at the Technical University of Loja, which dealt with the same laboratory implementation computer with LTSP.